Gate defects analysis in AlGaN/GaN devices by mean of accurate extraction of the Schottky Barrier Height, electrical modelling, T-CAD simulations and TEM imaging. (September 2017) - Tartarin, J.G.; Lazar, O.; Saugnon, D.; Lambert, B.; Moreau, C.; Bouexiere, C.; Romain-Latu, E.; Rousseau, K.; David, A.; Roux, J.L.
Abstract: This paper proposes an investigation focused on the Schottky diode related electrical behaviors on GaN high frequency technologies. As the Schottky diode represents the electrical input terminal (the command) of High Electron Mobility Transistors (HEMTs), this study also correlates with some first order degradation in the active channel (current IDS ). Non-invasive methods and related models have been used to determine the accurate Schottky Barrier Height (SBH) of the diode in terms of mean value and dispersion; this approach is convenient to evidence different failure mechanisms on virgin and stressed devices that can be correlated with DC or transient electrical parameters. It is shown that according to given temperature windows and IGS ranges, linear relationships can be extracted between the mean SBH and the inhomogeneities of the SBH that appear in forward-biased diode mode. This original approach permits to determine an increase or a decrease of the global SBH after a stress period. Electrical behaviors issued from the proposed non-destructive technique and from electrical modelling of the diode at different temperatures are found to be consistent with Transmission Electron Microscope (TEM) investigations. T-CAD models have also been used and tuned to account for the impact of interface fixed charge density changes on the electrical signatures of the HEMTs.